Does successful governance require heroes? The case of Sergio Fajardo and the city of Medellín: A reform case for instruction - Alejandro Fajardo; Matt Andrews (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The city of Medellín, Colombia was a cauldron of violence with 185 homicides per 100,000 people in 2002. By 2006, this rate had declined to 32.5. Such successful transformation was termed the 'Medellín miracle' and credited to policies of the city's mayor, Sergio Fajardo. Fajardo came to office in 2004 and led a series of reforms that observers call visionary. The story of Medellín's revival starts before Fajardo took office, however, and involved many more people than the mayor. This abridged version of the story offers instructors a classroom case to discuss leaders and leadership in governance reform.
Keywords: 330; Medellín; Colombia; leadership; reform; governance